Burnout and well‐being in otolaryngology trainees: A systematic review. Issue 2 (31st March 2022) - Lawlor, Skye K.; Low, Christopher M.; Carlson, Matthew L.; Rajasekaran, Karthik; Choby, Garret
Abstract: Objective: To comprehensively review the recent published literature to characterize current trends of burnout and well‐being among otolaryngology trainees. Methods: Study design: systematic review and meta‐analysis. A comprehensive literature review from 2000 to 2021 of studies related to otolaryngology resident burnout and well‐being, as well as the general topic of well‐being among surgical residents was completed. All included studies were summarized qualitatively. For the quantitative analysis, only articles reporting a Maslach burnout inventory (MBI), modified MBI or Mini‐Z‐ Burnout assessment were included. Results: Twenty‐five articles were included in the qualitative summary and nine articles in the quantitative analysis. In the qualitative summary, trainees were reported to have increased levels of distress and emotional hardening compared to attending otolaryngologists. Total hours worked per week and female gender were associated with worsened well‐being. Residency program strategies to improve trainee well‐being include program‐sponsored wellness activities, dedicated wellness champions, and assistance with clerical burden. Implementation of protected nonclinical time has been shown to decrease burnout and increase well‐being among trainees. Moreover, formal trainee mentorship programs have also been shown to reduce trainee burnout and stress. In the quantitative analysis, rates of trainee burnout ranged from 29.7% to 86% with an overall trend towards reduced rates of burnout from 2006 to 2021. Utilizing a weighted average, the overall burnout among otolaryngology residents was 58.6%. Conclusions: Rates of burnout remain high among otolaryngology trainees. Implementing formal mentorship programs and providing protected time during regular work hours appear to be effective tools to improve resident well‐being. Abstract : Burnout rates among otolaryngology trainees remain high but have improved from 2006‐2020. Highlights: Question: What is the current state of the literature in regard to otolaryngology trainee well‐being and burnout? Findings: In this systematic review of 34 articles, otolaryngology trainees were reported to have increased levels of distress and emotional hardening compared to attending otolaryngologists. Total hours worked per week and female gender were associated with worsened well‐being. Utilizing a weighted average, the overall burnout rate among otolaryngology residents was 58.6%. Implementation of protected nonclinical time has been shown to decrease burnout and increase well‐being among trainees. Meaning: Rates of burnout among otolaryngology trainees remains high but have improved over time. Formal mentorship programs and introduction of protected non‐clinical time may help to improve well‐being.